Characterization of a kg-scale archaeological lead-based PbWO4 cryogenic detector for the RES-NOVA experiment. (April 2023) - Beeman, J.W.; Benato, G.; Bucci, C.; Canonica, L.; Carniti, P.; Celi, E.; Clemenza, M.; D'Addabbo, A.; Danevich, F.A.; Di Domizio, S.; Di Lorenzo, S.; Dubovik, O.M.; et al.
Abstract: Core-collapse Supernovae (SNe) are one of the most energetic events in the Universe, during which almost all the star's binding energy is released in the form of neutrinos. These particles are direct probes of the processes occurring in the stellar core and provide unique insights into the gravitational collapse. RES-NOVA will revolutionize how we detect neutrinos from astrophysical sources, by deploying the first ton-scale array of cryogenic detectors made from archaeological lead. Pb offers the highest neutrino interaction cross-section via coherent elastic neutrino-nucleus scattering (CE ν NS). Such process will enable RES-NOVA to be equally sensitive to all neutrino flavours. For the first time, we propose the use archaeological Pb as sensitive target material in order to achieve an ultra-low background level in the region of interest ( O (1 keV)). All these features make possible the deployment of the first cm-scale neutrino telescope for the investigation of astrophysical sources. In this contribution, we will characterize the radiopurity level and the performance of a small-scale proof-of-principle detector of RES-NOVA, consisting in a PbWO 4 crystal made from archaeological-Pb operated as cryogenic detector. Highlights: RES-NOVA: first-proposed cryogenic detector made from archaeological lead for background suppression. Coherent elastic neutrino-nucleus scattering: innovative way to detect neutrinos from astrophysical sources. Radiopurity level measured on kg-scale prototype allows supernovae neutrino detection.